Advanced Asphalt Materials and Paving Technologies - Feipeng Xiao (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
There has been significant research progress in the area of pavement materials and paving technologies in the past decade. This includes the use of warm mix asphalt technologies, rubber asphalt, bio asphalt, nanomaterial applications, new construction technologies, innovative concrete materials, as well as the application of mechanistic-empirical pavement design. With all these developments, a collection of peer-reviewed articles with the theme of advanced asphalt materials and paving technologies is necessary for industry, researchers, government agencies, and other stakeholders. This collection promotes new technology, low costs, high durability, environmental friendliness, and effective resource usage in the area of advanced asphalt materials and paving technologies.